KEPUASAN KONSUMEN DITINJAU DARI KUALITAS PELAYANAN, STORE ATMOSPHERE DAN PROMOSI DI RUMAH MAKAN PONDOK JOWI SOLO - Shofia Zulfa Amalina; Sri Hartono; Ratna Damayanti (JURNAL ILMIAH EDUNOMIKA, 2020)
The purpose of this study was to analyze the effect of whether or not the quality of service, store atmosphere and promotion of consumer satisfaction at Pondok Jowi Restaurant Solo. The population in this study were consumers of Pondok Jowi Solo Restaurant in January 2020 at May 2020 with a total of 14,030 people. The sampling techniquemismpurposive samplingm which is a sampling technique with certain considerations by taking 100 respondents. Data collection uses a Likert scale questionnaire to measure respondents' answers to identify the relationship between service quality, store atmosphere and promotion of customer satisfaction. The results show that service quality, store atmosphere and promotion have a simultaneous and significant effect on customer satisfaction, servicei quality has assignificant effect on customer satisfaction, store atmosphere has a significant effect on customer satisfaction, and promotion has significant effect on customer satisfaction. Keywords: Service quality, Store atmosphere, Promotion, Consumer satisfaction